Humanistic geography in an indigenous community of Mexico: Santa Catarina Lachatao - García-Luna Romero, Ana C.; Quiroga-Garza, Angélica (Frontiers in Sustainable Cities, 2023)
The present study aim was to rethink the geographical reasoning of everyday life towards a new understanding of knowing how to think about space. This allowed establishing logical relations in spatial and socio-spatial distributions and uses of social phenomena, typical of Santa Catarina Lachatao, an indigenous Mexican community in Sierra Norte Zapoteca. Based on ethnographic qualitative research methods along with a total of three visits lasting 15 weeks, the daily experience of people and their community in different times and spaces, experiences, perspectives, and prejudices, were studied. The geographical approach (cartographies) reflects the social construction of the spatial components as the basic understanding of the territory from everyday life. In this study we worked on the indigenous citizenship and its territory, analyzing, and contrasting social phenomena such as power-subjection, wealth-poverty, and exclusion-inclusion that transversally allow us to reflect and understand some of the characteristics of diversity and territoriality of the indigenous communities in Mexico. The result derives from recognizing features and characteristics that predominating in indigenous communities and that is evident in the social production of their public space.